Cross-Generational Customer Journey Analysis: Unveiling Instagram's Effectiveness in Clinic Marketing - Husen, Abeng Anandri; Arini, Merita; Wan Mamat, Wan Hasliza (Universitas Muhammadiyah Yogyakarta, 2024)
The rise in private primary care necessitates clinic entrepreneurs to innovate and improve clinic performance through effective marketing, particularly through social media platforms like Instagram. The digital era presents challenges due to the simultaneous presence of five generations: baby boomers, generation X, generation Y, generation Z, and generation Alpha, each with unique attitudes, preferences, and behaviors. This research aims to explore the effectiveness of Instagram as a clinic marketing platform across generations in a private clinic. Method: A cross-sectional design was conducted in this research. Data was collected using a consecutive sampling method among the Instagram clinic’s followers (n = 377). The collected data is then analyzed using the percentage value of customer path 5A attributes, conversion rate, purchase action ratio (PAR), brand advocacy ratio (BAR), and one-way ANOVA. The percentage value of customer path 5A attributes showed a good result in four generations, including the conversion rate scores. PAR and BAR scores have optimal results in four generations. There was a significant difference in 5A attributes, PAR, and BAR (p<0.05). Instagram is an effective social media platform for clinical marketing for every generation. This study contributes to reassuring clinic entrepreneurs to utilize Instagram as their marketing platform.